Nutraceuticals as Potential Chemopreventive Agents: A Review - Bhatia, Vidhi J.; Nair, Sreeja S. (Natural Products Journal, The, 2018)
Background: Recent years have seen a rise in the number of cancer cases and deaths worldwide. Emphasis on prevention as an approach for the management of cancer has increased. The chemopreventive intervention prevents, suppresses, or reverses the initiation of carcinogenesis or the progression of already initiated, neoplastic cells to invasive cancer. Investigating the effects of potential preventive interventions is a central goal in cancer preventive research. Objective: This review aims to present the natural chemopreventive agents with their proposed mechanism of action to prevent cancer. Method: Research and review papers were analyzed and the data were compiled to present the potential mechanisms of various nutraceuticals for chemoprevention. Data was also obtained from WHO site. Result: 96 articles including research and review papers were referred which proves various nutraceuticals to be potential chemopreventive agents. Mechanisms of chemoprevention were discussed in detail in the research articles. Review articles provided a brief description of the drugs. Conclusion: The findings from this review article confirm the potential activities of various nutraceuticals in prevention of cancer and management strategies. There is need for more clinical research on the different plant species to identify the active constituents, their possible mechanisms as well as their potential in the prevention of cancer.
Keywords: toxicity